2023
DOI: 10.1021/acs.est.2c08835
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Neutral PFAS for Potential Dermal Absorption from the Gas Phase

Abstract: Exposures to per- and polyfluoroalkyl substances (PFAS) are of increasing concern. Assessments typically focus only on ingestion and inhalation exposure due to a lack of generally accepted approaches for estimating dermal absorption. Prior work indicates limited dermal absorption of ionic PFAS, but absorption of neutral PFAS has not been examined from the liquid vehicle or from vapor. Partitioning of semivolatile organic compounds from the gas phase to the skin surface (i.e., stratum corneum) is well known, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Figure S10 shows a plot for 134 neutral PFAS using the log K aw and log K ow values predicted by COSMO therm . These neutral PFAS are from the lists of Kissel et al and our previous study . The data points are even more widely distributed, although the plot again shows that air is the most important phase and that the air/organic phase distribution can be an important fate determinant, except for short-chain polar PFAS, which can also be in water.…”
Section: Resultsmentioning
confidence: 55%
“…Figure S10 shows a plot for 134 neutral PFAS using the log K aw and log K ow values predicted by COSMO therm . These neutral PFAS are from the lists of Kissel et al and our previous study . The data points are even more widely distributed, although the plot again shows that air is the most important phase and that the air/organic phase distribution can be an important fate determinant, except for short-chain polar PFAS, which can also be in water.…”
Section: Resultsmentioning
confidence: 55%
“…While listed PFAS ingredients appear relatively non-bioaccessible compared to residual PFCAs using artificial sweat, these substances may still pose a risk, either from direct dermal absorption from the gas phase (as predicted by Kissel et al , for volatile PFAS), or indirect exposure following transformation in the environment to persistent PFAAs. 27 In comparison, PFAAs were readily bioaccessible, indicating that despite occurring at orders of magnitude lower concentrations than listed ingredients, they can nevertheless be relevant for dermal exposure. Clearly, the main limitation in this study was that our SSFL composition did not include sebum, which was previously shown to enhance bioaccessibility, in particular for more hydrophobic PFAS.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, clothing as a secondary PFAS source could potentially facilitate dermal PFAS exposures and prolong indoor inhalation exposures. Generally, dermal absorption of PFAS has been considered a minor route of exposure compared to other pathways, i.e., dietary intake and drinking water, because dermal permeability has been thought to be low for PFAS. ,,,, However, a recent study found that direct transdermal absorption of PFAS from air may be of greater relevance than inhalation exposure for multiple neutral PFAS . Based on the estimates of the dermal uptake-to-inhalation (D/I) ratio reported by Kissel et al and the criteria established by Weschler and Nazaroff, dermal absorption is not expected to exceed inhalation exposure but is expected to contribute non-negligibly to MeFOSE and EtFOSE uptake.…”
Section: Resultsmentioning
confidence: 99%
“…1,24,48,77,78 However, a recent study found that direct transdermal absorption of PFAS from air may be of greater relevance than inhalation exposure for multiple neutral PFAS. 79 Based on the estimates of the dermal uptake-toinhalation (D/I) ratio reported by Kissel et al 79 and the criteria established by Weschler and Nazaroff, 80 dermal absorption is not expected to exceed inhalation exposure but is expected to contribute non-negligibly to MeFOSE and EtFOSE uptake. Such dermal absorption from air can be mediated by PFAS sorbed to clothing.…”
Section: ■ Results and Discussionmentioning
confidence: 99%